Synthesis and development of inverse-type nucleoside diarylethene photoswitches - Hendrich, Christoph; Reinschmidt, Martin; Büllmann, Simon; Kolmar, Theresa; Jäschke, Andres (Chemistry - a European journal, 2024)
Nucleosidic diarylethenes (DAEs) have evolved from an emerging class of photochromes into a well-established option for integrating photochromic functionalities into biological systems. However, a comprehensive understanding of how chemical structure influences their photochromic properties remains essential. While structural features, such as an inverse connection between the aryl residues and the ethene bridge, are well-documented for classical DAEs, their application to nucleosidic DAEs has been underexplored. In this study, we address this gap by developing three distinct types of inverse nucleosidic DAEs-semi-inverse thiophenes, semi-inverse uridines and inverse uridines. We successfully synthesized these compounds and conducted comprehensive analyses of their photostationary states, thermal stability, reversibility, and reaction quantum yields. Additionally, we conducted an in-depth comparison of their photochromic properties with those of their normal-type counterparts. Among the synthesized compounds, seven semi-inverse thiophenes exhibited the most promising characteristics. Notably, these compounds demonstrated excellent fatigue resistance, with up to 96 % retention of photochromic activity over 40 switching cycles, surpassing the performance of all comparable nucleosidic DAEs reported to date. These findings hold significant promise for future applications in various fields.
Gesehen am 27.02.2025